Hak Waris Khunṡa dan Metode Penyelesaiannya dalam Hukum Waris Islam - Muhibbussabry (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The heirs and their shares in Islamic inheritance law have been rigidly regulated in the Qur'an, hadeeth and ijma', everyone who has a relationship of marriage, descent, and kinship, whether the status is still in the womb, male and female have their respective rights and shares. However, in reality of life, there are heirs whose status is unclear because they have multiple sexes (khunṡa), so that the share of inheritance received cannot be determined with certainty. The purpose of this study is to find out the inheritance rights of khunṡa, the opinion of the mażhab scholars and the calculation method for resolving khunṡa cases in detail. This research uses an analytical descriptive method with a qualitative approach. The results of this study identify two types of khunṡa: first, khunṡa ghairu musykil, whose inheritance is determined by the method of urination. If it is through the male sex, it inherits the male share; if it is female, it inherits the female share. If it is through both sexes, it is determined by the sex that urinates first, because it is considered the original identity. If it comes out at the same time, it is determined by the greater volume. Secondly, khunṡa musykil is divided into two conditions: first, when it is still possible to clarify the status of khunṡa because she has not yet reached puberty. In this case, he and the other heirs are given the smallest share of the two estimates of a male or female, with the rest of the estate deferred until the status of the khunṡa becomes clear. Secondly, when it is no longer possible to clarify the status of the khunṡa because he has reached puberty, but he does not have the characteristics of a male or female. In this situation, he and the other heirs are given half of the two estimates of male or female. This share calculation can be the best alternative in resolving khunṡa inheritance cases because there is still a legal vacuum in the compilation of Islamic law in Indonesia.